The impact of low emission zones on PM10 levels in urban areas in Germany - Christiane Malina; Frauke Fischer (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2012)
High levels of particulate matter scaling less than 10 micrometers in diameter (PM10) in many urban areas have led to the introduction of binding PM10 limit values by the European Commission in 2005. Road transport in inner city areas is believed to be one of the main contributors to accumulated PM10 levels and, thus, is the focus of regulation. One of the strongest regulatory mechanisms to meet the new PM10 air quality standard is the introduction of low emission zones (LEZs) in Germany. This policy allows local authorities to define geographical areas in urban agglomerations as LEZs, into which vehicles that do not meet predetermined emission standards are prohibited from entering. This paper evaluates the effectiveness of LEZs on reducing PM10 levels in German cities. We employ a fixed effects panel data model to analyze the effects of LEZs on daily PM10 levels using data from 2000 to 2009. We take into account daily data for meteorological conditions and traffic volume. The results of the analysis reveal that the introduction of LEZs has significantly reduced daily PM10 levels in urban areas. We can also show that PM10 levels are significantly driven down further when LEZ standards in cities become more stringent over time.
Keywords: Q58; R49; 330; Particulate matter; low emission zones; panel data